A real-time fluorescence polarization activity assay to screen for inhibitors of bacterial ribonuclease P. Issue 20 (23rd September 2014) - Liu, Xin; Chen, Yu; Fierke, Carol A.
Abstract: Ribonuclease P (RNase P) is an essential endonuclease that catalyzes the 5′ end maturation of precursor tRNA (pre-tRNA). Bacterial RNase P is an attractive potential antibacterial target because it is essential for cell survival and has a distinct subunit composition compared to the eukaryal counterparts. To accelerate both structure-function studies and discovery of inhibitors of RNase P, we developed the first real-time RNase P activity assay using fluorescence polarization/anisotropy (FP/FA) with a 5′ end fluorescein-labeled pre-tRNA Asp substrate. This FP/FA assay also detects binding of small molecules to pre-tRNA. Neomycin B and kanamycin B bind to pre-tRNA Asp with a K d value that is comparable to their IC 50 value for inhibition of RNase P, suggesting that binding of these antibiotics to the pre-tRNA substrate contributes to the inhibitory activity. This assay was optimized for high-throughput screening (HTS) to identify specific inhibitors of RNase P from a 2880 compound library. A natural product derivative, iriginol hexaacetate, was identified as a new inhibitor of Bacillus subtilis RNase P. The FP/FA methodology and inhibitors reported here will further our understanding of RNase P molecular recognition and facilitate discovery of antibacterial compounds that target RNase P.